# Solve for c 92^2+92^2=c^2 922+922=c2
Rewrite the equation as c2=922+922.
c2=922+922
Take the square root of both sides of the equation to eliminate the exponent on the left side.
c=±922+922
The complete solution is the result of both the positive and negative portions of the solution.
Simplify the right side of the equation.
Raise 92 to the power of 2.
c=±8464+922
Raise 92 to the power of 2.
c=±8464+8464
c=±16928
Rewrite 16928 as 922⋅2.
Factor 8464 out of 16928.
c=±8464(2)
Rewrite 8464 as 922.
c=±922⋅2
c=±922⋅2
Pull terms out from under the radical.
c=±922
c=±922
The complete solution is the result of both the positive and negative portions of the solution.
First, use the positive value of the ± to find the first solution.
c=922
Next, use the negative value of the ± to find the second solution.
c=-922
The complete solution is the result of both the positive and negative portions of the solution.
c=922,-922
c=922,-922
c=922,-922
The result can be shown in multiple forms.
Exact Form:
c=922,-922
Decimal Form:
c=130.10764773…,-130.10764773…
Solve for c 92^2+92^2=c^2

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top